2015
DOI: 10.1136/bjsports-2014-094228
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effects of upper body warm-up on performance and injury

Abstract: Purpose This systematic review was conducted to identify the impact of upper body warm-up on performance and injury prevention outcomes. Methods Web of Science, MEDLINE, SPORTDiscus, PsycINFO and Cochrane databases were searched using terms related to upper extremity warm-up. Inclusion criteria were English language randomised controlled trials from peer-reviewed journals in which investigation of upper body warm-up on performance and injury prevention outcomes was a primary aim. Included studies were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 38 publications
1
67
0
9
Order By: Relevance
“…Bu çalışmada olduğu gibi core kuvvetten çok core stabilizasyonu arttırmaya yönelik antrenman uygulamalarının sakatlığı azaltma etkisi kabul edilirken (Lehman, 2006), atletik etkisi için bulgular yeterli kabul edilmeyebilir (Hibbs, Thompson, French, Wrigley, & Spears, 2008). Fakat İyi antrene edilmiş core bölgenin optimum güç üretimini sağladığı gibi, fonksiyonel atletik performans için, gücün ve hareketlerin aktarımını sağladığı kabul edilmektedir (Akuthota & Nadler, 2004;Dendas, 2010;W. Ben Kibler, Press, & Sciascia, 2006).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Bu çalışmada olduğu gibi core kuvvetten çok core stabilizasyonu arttırmaya yönelik antrenman uygulamalarının sakatlığı azaltma etkisi kabul edilirken (Lehman, 2006), atletik etkisi için bulgular yeterli kabul edilmeyebilir (Hibbs, Thompson, French, Wrigley, & Spears, 2008). Fakat İyi antrene edilmiş core bölgenin optimum güç üretimini sağladığı gibi, fonksiyonel atletik performans için, gücün ve hareketlerin aktarımını sağladığı kabul edilmektedir (Akuthota & Nadler, 2004;Dendas, 2010;W. Ben Kibler, Press, & Sciascia, 2006).…”
Section: Discussionunclassified
“…Bu çalışmaya benzer bir çalışmada 6 haftalık kuvvet antrenmanları(core kuvvet, elastik direnç, sağlık topu egzersizleri) sonucunda genç tenisçilerde servis hızı kontrol grubuna göre anlamlı şekilde artarken, servis isabeti değişmemiştir (Fernandez-Fernandez et al, 2013). Benzer şekilde vuruş ve fırlatma hızına ilişkin(omuz eklemlerine ait) çalışmaların birçoğunda core egzersizlerin olumlu etkileri açıkça ortaya koyulmuştur.…”
Section: Discussionunclassified
“…Warm-up is generally performed previously to exercise to increase performance, however the literature has shown in most studies that warm-up does not change 1,2 . We have previously shown that warm-up did not influence performance on different exercise protocols 14.15 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, warm-up was not capable of changing performance in maximal cycling. Indeed, low to moderate intensities of warm-up present mostly neutral effects on performance of several variables, such as strength and power 1 . However, despite the lack of change on performance, warm-up is able to change blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation